علاقة بعض العوامل الأسرية بمشكلات التلاميذ السلوكية - مصطفى طلال; قاسم عنان (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study aims at realizing the relationship between some family factors and problems related to pupils’ behavior as to define the most widespread problems among pupils. The first chapter handles the problem of the studyand its importance, the objectives of the study, previous studies, the concepts and terminologies of the study, and the scientific methodology used.The second chapter of this study deals with the relationship between pupils and their social environment including their relationship with their family (their parents and their brothers), their relationship with their school (dynamic relationship between children and school and between parents and school.) . The study provides in the third chapter an analysis of the results of the field study based on questionnaire as an essential tool by directing it to the pupils themselves in the schools of the townof JawbatBerghäll - the second stage of basic education. The results of the study show that the social problems among males are more than those among females. Those problems are evident among higher classes compared to lower ones. It is also noted that problems are deeper among pupils whose parents’ education level is lower. The conclusion of this research is a set of suggestions based on the analysis of the results. هدفت هذه الدراسة إلى معرفة علاقة بعض العوامل الأسرية بمشكلات التلاميذ السلوكية ,ومعرفة أكثر هذه المشكلات شيوعاً لدى التلاميذ موضع الدراسة , وقد تناولت في فصلها الأول مشكلة الدراسة وأهميتها, أهداف الدراسة,الدراسات السابقة, مفاهيم ومصطلحات الدراسة,المنهجية العلمية المتبعة.وتستعرض الدراسة في فصلها الثاني علاقة التلميذ ببيئته الاجتماعية متضمناً علاقة التلميذ بأسرته(والديه,إخوته),وعلاقته بمدرسته(دينامية العلاقة بين الطفل والمدرسة,وبين الأهل والمدرسة). وتقدم الدراسة في فصلها الثالث تحليلاً لنتائج الدراسة الميدانية معتمداً الأستبانة أداة أساسية بتوجيهها إلى التلاميذ أنفسهم في مدارس ناحية جوبة برغال – الحلقة الثانية,وقد أظهرت نتائج الدراسة أن نسبة المشكلات السلوكية لدى الذكور أكثر من الإناث,ولدى الصفوف العليا أكثر من الدنيا,ولدى التلاميذ ممن مستوى تعليم الوالدين ابتدائيومادون أكثر ممن مستوى تعليم الوالدين جامعيومافوق,وخلص البحث استناداً لتحليل النتائج إلى مجموعة من المقترحات.